Crevicular fluid biomarkers and periodontal disease progression. (12th December 2013) - Kinney, Janet S.; Morelli, Thiago; Oh, Min; Braun, Thomas M.; Ramseier, Christoph A.; Sugai, Jim V.; Giannobile, William V.
Abstract Aim Assess the ability of a panel of gingival crevicular fluid (GCF) biomarkers as predictors of periodontal disease progression (PDP). Materials and methods In this study, 100 individuals participated in a 12‐month longitudinal investigation and were categorized into four groups according to their periodontal status. GCF, clinical parameters and saliva were collected bi‐monthly. Subgingival plaque and serum were collected bi‐annually. For 6 months, no periodontal treatment was provided. At 6 months, patients received periodontal therapy and continued participation from 6 to 12 months. GCF samples were analysed by ELISA for MMP‐8, MMP‐9, Osteoprotegerin, C‐reactive Protein and IL‐1β. Differences in median levels of GCF biomarkers were compared between stable and progressing participants using Wilcoxon Rank Sum test (p = 0.05). Clustering algorithm was used to evaluate the ability of oral biomarkers to classify patients as either stable or progressing. Results Eighty‐three individuals completed the 6‐month monitoring phase. With the exception of GCF C‐reactive protein, all biomarkers were significantly higher in the PDP group compared to stable patients. Clustering analysis showed highest sensitivity levels when biofilm pathogens and GCF biomarkers were combined with clinical measures, 74% (95% CI = 61, 86). Conclusions Signature of GCF fluid‐derived biomarkers combined with pathogens and clinical measures provides a sensitive measure for discrimination of PDP (ClinicalTrials.gov NCT00277745).